MAQĀṢIḌ SHARĪ’AH SEBAGAI METODE PENGGALIAN HUKUM ISLAM: ANTARA AL-GHAZĀLĪ, AL-SHAṬIBĪ, DAN AL-ṬŪFĪ - Thahir, A. Halil (EMPIRISMA: JURNAL PEMIKIRAN DAN KEBUDAYAAN ISLAM, 2016)
Islam comes to bring goodness to mankind. In practice Islamic law must deal with new issues that demand new legal solutions as well. It is often that a partial legal approach produces partial legal products by altering the welfare that is at the heart of Islamic Sharī’ah. The maqāṣid al-sharī’ah approach can be a way for the development of Islamic law which is oriented towards human welfare so that Islam as raḥmatan lil-‘ālamīn can really be realized. This article seeks to examine the development of the concept of maqāṣid al-sharī’ah by emphasizing the characteristic of the three main figures of different schools of thought: al-Ghazālī, al-Shaṭibī, al-Ṭūfī. Keywords: Maqāṣid al-Sharī’ah, Maṣlaḥah, Islamic Law